The Relationship Between Vocabulary Exposure and Vocabulary Recognition Among EFL Students - Nur Afiah Ibrahim; Andi Bulkis Magfirah Mannong (Balla' Caradde Education, 2026)
Vocabulary mastery is essential for English language proficiency; however, limited classroom exposure continues to hinder EFL learners' lexical development. Given the growing role of digital media in language learning, this study investigates the relationship between extramural vocabulary exposure and vocabulary recognition among English Education students. Using a quantitative correlational design, data were collected from 20 students at Universitas Muhammadiyah Makassar (2025/2026) through a questionnaire on vocabulary exposure via digital media and a multiple-choice vocabulary recognition test. Spearman Rank Correlation analysis revealed a strong, positive, and statistically significant relationship between vocabulary exposure and vocabulary recognition (r = 0.709, p < .001). The findings highlight the value of informal digital learning environments in fostering vocabulary acquisition beyond classroom instruction. This study contributes empirical evidence supporting the integration of autonomous, media-based vocabulary learning into EFL pedagogy, offering practical insights for educators seeking to strengthen students' lexical competence.